Perancangan Sistem Keamanan Kain Tradisional Lampung Berbasis Sensor PIR - Yuniati, Yetti (Department of Electrical Engineering, Faculty of Engineering, Universitas Lampung, 2022)
Abstract The museum is a place to store historical relics that are very important as evidence that these relics are true. Museums are also a means for a country to show the public about the relics of historical objects which are treasures and must be preserved. Lampung Province State Museum, is one of the museums in Indonesia. One of the relics that must be preserved in this museum is the traditional Lampung cloth which is still there and is a legacy for the people of Lampung. The Lampung Museum has a collection of traditional Lampung fabrics whose safety conditions are still a problem for the Lampung Museum management, where there is a lack of care and it is easy for visitors to touch and change the layout of these items. This can cause damage and changes to the collectible. Therefore, the Passive Infra Red (PIR) sensor-based Security System is a tool designed to maintain the security system of the Lampung Province State Museum object